Criminalization of Public Policy Without Mens Rea in Corruption Offenses: A Case Study of Sugar Import Policy - Octarina, Nynda Fatmawati; Maspaitella, Leonardo Benito (Al-Risalah, 2026)
Criminal liability is grounded in the principle of geen straf zonder schuld, which requires the presence of both actus reus and mens rea to establish guilt. However, in the enforcement of corruption law in Indonesia, evidentiary practices tend to prioritize state financial losses and abuse of authority, often sidelining the assessment of the perpetrator’s mental element. This reveals a critical gap between doctrinal principles and judicial practice, particularly in cases involving public policy decisions. This study aims to examine the position of mens rea in the evidentiary framework of corruption crimes and to analyze the criminal liability of public officials in the absence of proven intent, as reflected in the sugar import policy case. Using normative legal research with statutory, conceptual, and case approaches, this study analyzes Decision of the Central Jakarta District Court Number 34/Pid.Sus-TPK/2025/PN Jkt.Pst. The findings indicate that although mens rea in Indonesian criminal law is doctrinally reflected through intent and negligence, judicial reasoning in corruption cases tends to adopt a formalistic approach by emphasizing procedural violations and state losses. This study argues that such an approach leads to the criminalization of public policy in the absence of proven culpability. The novelty of this research lies in its critique of the shift from a culpability-based system toward a loss-based liability model in corruption cases. It concludes that state losses arising from policy decisions without intent to unlawfully benefit should be understood as occupational risks rather than grounds for criminal punishment, thereby reaffirming the centrality of mens rea in criminal liability.